Peran Indonesian Migrant Workers Union Netherland Dalam Melindungi Tenaga Kerja Indonesia Ilegal di Belanda - Angik Ndaru Sahasti (HI 16 UMY 115, 2016)
*115 This study aims to explain the role of Indonesian Migrant Workers Union Netherland (IMWU-NL)In Protecting the Indonesian Illegal Workers in the Netherlands. This study used qualitative design to gather a description of the role IMWU NL. Mechanical methods of collecting data Technique of data collection method is is secondary data. Secondary data use literature material such as books, journals, and articles. Researchers also supports data by downloading data at multiple sites on the internet that are relevant to the purpose of research. This study discusses the analytical explanation of the role of the Indonesian Migrant Workers Union Netherland to the existence of Indonesian Illegal Workers in the Netherlands. Indonesian Migrant Workers Union Netherland (IMWU-NL) Indonesian Workers Union that seeks to protect the Indonesian Workers in the Netherlands, especially the illegal Workers. Illegal Indonesian Workers is an individual who illegally work in the Netherlands without a license to comes, Life and works In the Netherland and is regarded as a threat to the Dutch government. IMWU-NL to the protection of Indonesian Illegal Workers in the Netherlands through an international network PICUM. IMWU-NL actively participate in PICUM network to fight for basic rights for Indonesian illegal Workers in the Netherlands.